The verandahway of the traditional shophouses in Kuala Lumpur : its usage and role in contributing to the K.L. Urban streetscape. - Shahril, Sharif (1988)
This particular study is done to analyse the usage and role played by the verandahway in Kuala Lumpur generally and concentrating on Jin., Tuanku Abdul Rahman as one of the most rapidly develope in the process of urban renewal.